Water safety plan implementation in East Africa: Motivations and barriers - Parker, Alison; Summerill, Corinna (Intermediate Technology Publications, 2013)
Water safety plans (WSPs) are a comprehensive source-to-tap risk management approach that are recognized as the most effective way of ensuring drinking water safety. In East Africa there is only one utility implementing them, so this research aims to identify barriers for WSP implementation in this region, as well as potential motivating factors. This is achieved through 20 semi-structured interviews with utilities, regulators, and international agencies. The biggest motivating factor was the potential of WSPs to improve standards and reduce water quality incidents, with the potential for cost savings and non-revenue water reduction as further motivations. However, in many utilities senior managers are not motivated to start implementing WSPs and they can prevent other staff from doing so. Smaller or weaker utilities may struggle to implement a WSP as they are constantly engaged in their day-to-day problems and do not have the capacity to plan for the longer term.